Talent show tricks - Dixon, Franklin W. (Dixon, Franklin W. Hardy Boys clue book, 2016)
"Frank and Joe are excited for the school's annual talent show! Frank is working backstage, and Joe is going to show off his sweet juggling skills. Someone keeps playing pranks on all the acts-- bubbles are found in someone's trumpet and someone's music is replaced with the sound of croaking frogs!"--Jacket.